1962
DOI: 10.1042/bj0840364
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxic liver injury. nicotinamide-adenine dinucleotide-pyrophosphorylase activity of nuclei isolated from rat liver in heliotrine and in dimethylnitrosamine poisoning

Abstract: 2. The nunmber of reactive SH groups/molecule in the haemoglobins studied approximate either to 2 or to 4. 3. The behaviour of the reactive SH groups differs from that of cysteine in three ways: (a) the rate of reaction of heavy-metal ions with the reactive SH groups is slower than with cysteine; (b) thiosulphate interferes with the reaction between Ag+ ions and the reactive SH groups of human haemoglobin, but not with cysteine; (c) the acid-base-titration curves of human haemoglobin in the presence and absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1963
1963
1991
1991

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Refeeding after protein starvation enhances RNA polymerase levels (68). It has also been reported that DPN pyrophosphorylase activity is diminished by poisoning with berylliuni (66) and heliotrine (71) and also in tumor tissues (142), but not after carbon tetrachloride, ethionine (66), and dimethyl nitrosoamine (66,71).…”
Section: The Chromatin Spacementioning
confidence: 94%
“…Refeeding after protein starvation enhances RNA polymerase levels (68). It has also been reported that DPN pyrophosphorylase activity is diminished by poisoning with berylliuni (66) and heliotrine (71) and also in tumor tissues (142), but not after carbon tetrachloride, ethionine (66), and dimethyl nitrosoamine (66,71).…”
Section: The Chromatin Spacementioning
confidence: 94%
“…after partial hepatectomy, whereas no significant changes were caused by the administration of various toxic substances, even when liver nuclei were obviously damaged (Stirpe & Aldridge, 1961). The lack of effect of one of these poisons, dimethylnitrosamine, was confirmed by Christie, Bailie & Le Page (1962), who observed also a decreased activity of the enzyme in liver nuclei after heliotrine poisoning. The results obtained with regenerating liver were confirmed by the late Professor R. K. Morton (personal communication to Dr W. N. Aldridge) and by Jones & Waravdekar (1965) by a histochemical method, but no changes were observed in the enzyme activity determined in the whole homogenate from regenerating rat liver (Myers, 1962) or in nuclei isolated in non-aqueous media from 29hr.-regenerating rat liver (Siebert, 1963, footnote at p. 405, and personal communication).…”
mentioning
confidence: 96%